Food Delivery Services and Customer Preference in Kathmandu Valley - Joshi, Arya; Byahut, Bikash; Pradhan, Sumit (Nepalese Journal of Business, 2025)
This study examines the food delivery services and customer preference in Kathmandu Valley. Customer preference is the dependent variable. The selected independent variables are past experience, variety of choice, timely delivery, price, quality of food, and packaging. The primary source of data is used to assess the opinions of the respondents regarding past experience, variety of choice, timely delivery, price, quality of food, packaging, and preference. The study is based on primary data of 116 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of food delivery services and customer preference in Kathmandu Valley. The study showed that past experience has a positive impact on customer preference. It indicates that reliable information about the food delivery leads to increase in customer preference towards food delivery. Similarly, variety of choice has a positive impact on customer preference. It indicates that availability of the variety of choice, higher would be the customer preference. Likewise, timely delivery has a positive impact on customer preference. It indicates that transporting goods to the recipient within the promised or expected time frame leads to increase in customer preference. In addition, price has a positive impact on customer preference. It indicates that affordable price leads to increase in customer preference. Further, quality of food has a positive impact on customer preference. It indicates that higher the quality of food, higher would be the customer preference. Moreover, packaging has a positive impact on customer preference. It indicates that attractive packaging of the products leads to increase in customer preference.